2017
DOI: 10.3350/cmh.2016.0059
|View full text |Cite
|
Sign up to set email alerts
|

Transient elastography versus hepatic venous pressure gradient for diagnosing portal hypertension: a systematic review and meta-analysis

Abstract: Background/AimsTransient elastography (TE) has been proposed as a promising noninvasive alternative to hepatic venous pressure gradient (HVPG) for detecting portal hypertension (PH). However, previous studies have yielded conflicting results. We gathered evidence from literature on the clinical usefulness of TE versus HVPG for assessing PH.MethodsWe conducted a systematic review by searching databases for relevant literature evaluating the clinical usefulness of non-invasive TE for assessing PH in patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…Serum platelet count and LSM strongly correlate with fibrosis stage and portal hypertension . LSM has proven accuracy for discriminating patients with and without clinically significant portal hypertension, with a mean area under the receiver operating curve of 0.93 in a meta‐analysis . LSM and platelet count are simple, non‐invasive and objective variables.…”
Section: Discussionmentioning
confidence: 99%
“…Serum platelet count and LSM strongly correlate with fibrosis stage and portal hypertension . LSM has proven accuracy for discriminating patients with and without clinically significant portal hypertension, with a mean area under the receiver operating curve of 0.93 in a meta‐analysis . LSM and platelet count are simple, non‐invasive and objective variables.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, HVPG measurement has been considered as the reference of standard method for evaluating and grading of PH . Even though several non‐invasive methods such as transient elastography showed fair diagnostic accuracy to detect CSPH, HVPG measurement should remain as gold standard for the diagnosis of CSPH, and HVPG has been one of the most accurate surrogate indicator of prognosis in cirrhosis patients . However, due to invasive nature of examination and need of special equipment and skilled expertise, the widespread routine clinical use of HVPG measurement has been limited .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, measurement of the hepatic venous pressure gradient (HVPG) is considered as reference of standard method for evaluating PH, and HVPG ≥ 10 mmHg indicates the presence of clinically significant PH (CSPH) . In addition, HVPG has been considered as the best surrogate indicator of prognosis in patients with cirrhosis . However, HVPG measurement is invasive examination with procedure related complication although the incidence of complication is quite low (<1% of patients) and the nature of complication is minor such as transient cardiac arrhythmias, local pain, and vagal reaction in most of patients; thus, HVPG is not routinely done in all centers .…”
Section: Introductionmentioning
confidence: 99%
“…As variceal bleeding is the most important complication of PH, the relationship between TE values and the presence of esophageal varices has been also investigated in several studies [13,21,22], which reported significant correlations between TE values and the presence of esophageal varices. Furthermore, Kim et al [23] conducted a systematic review and meta-analysis to identify the clinical usefulness of non-invasive TE for assessing PH as an alternative to HVPG in patients with CLD. The diagnostic accuracy of TE for CSPH was high (correlation 0.7480, 95% confidence interval: 0.6464; 0.8236, P <0.0001).…”
mentioning
confidence: 99%
“…Although a systematic review and meta-analysis by Kim et al [23] showed the overall clinical usefulness of non-invasive TE for assessing PH as an alternative to HVPG in patients with CLD, that study had potential limitations. First, only eight studies were included, so the robustness of the conclusions in terms of the evaluation of the usefulness and performance of TE might be limited.…”
mentioning
confidence: 99%